Evaluation and Professional Development of Teachers in Greece - Giorgos Maggopoulos; Konstantia Svarna (Language, Literature and Education: Research Updates Vol. 3, 2025)
The educational evaluation is a set of organized and systematic actions that aim to achieve the goals of education. Additionally, this is a tool that assesses the degree of achievement of predetermined objectives, provides feedback to the teacher, identifies methods for shaping the teaching approach, and improves self-awareness. The purpose of this study is to explore the views of teachers regarding their evaluation and professional development. The preferred methodology is a qualitative approach which has used the semi-structured interview as a data collection technique with a sample of ten primary school teachers. The participating teachers have been working in public education from four to thirty-five years, while four of them serve as substitutes. With regard to the first research question, the categories of the analysis were created from the thematic analysis (atlas) of the data, literal, interpretative, and reflective aspects. The respondents considered the main purpose of their evaluation to be the improvement that results from the interlinkage between the identification of weaknesses and the implementation of training interventions. As far as the evaluation criteria are concerned, they mainly highlighted the teacher’s professional skills, the learning environment, and the consistency of service. Persons close to the teacher, such as the director, colleagues, the teachers themselves, and the Education Advisor are considered to be the most appropriate actors of their evaluation. According to the findings, the benefits of the evaluation include the rewarding of the teachers and the recognition of their work, as well as the establishment of a culture of evaluation, while the disadvantages include negative emotions and unfair practices (e.g., stress, fear, pressure, insecurity, competition), negative consequences (e.g., salary reduction, dismissal), categorization of teachers and additional workload. Professional development is regarded as extremely useful and necessary and is achieved through formal, non-formal, or informal processes. It helps teachers to acquire additional qualifications, knowledge and skills that enhance their role, improve their work, and, above all, strengthen their professional identity. Finally, the respondents considered that the teachers’ evaluation is directly linked to their professional development, as the former feeds the latter.